Evaluation of the Antibacterial Activity of Methanol Extracts from Leaves, Bark, and Fruit of Jambu Bol (Syzygium malaccense L.) - Efendi, M. Rifqi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2025)
Syzygium malaccense L., commonly known as Malay apple, is a medicinal plant traditionally used to treat various infectious diseases. This study aimed to compare the antibacterial activity of methanol extracts from the leaves, bark, and fruit of S. malaccense against Escherichia coli and Staphylococcus aureus. Each extract was characterized through organoleptic observations, moisture content determination, total ash content analysis, and phytochemical screening. Antibacterial activity was evaluated using the agar diffusion method, with dimethyl sulfoxide (DMSO) as the negative control and chloramphenicol (30 µg/disc) as the positive control. Phytochemical screening confirmed the presence of phenolic compounds, alkaloids, flavonoids, and saponins in all extracts. The antibacterial assay revealed that all tested extracts exhibited inhibitory effects against both bacterial strains, with inhibition zones ranging from 8.15 to 13.12 mm. The methanol extract of S. malaccense bark demonstrated the highest antibacterial activity at a 20% concentration, producing a 13.12 mm inhibition zone against S. aureus.